Political Violence in Interwar France - Millington, Chris ca. 20./21. Jh. (History compass, 2012)
Political violence in interwar France is largely considered a marginal phenomenon, the practice of fascist and communist groups alien to the democratic and Republican consensus. Save for the occasional outburst of mass violence, historians have dismissed the sharp political conflict of the interwar years as pretense and bluster confined to the pages of newspapers and thunderous speeches. This article argues that the routine occurrence of political violence in France deserves greater attention. It suggests that analysis of the mechanics of daily confrontation such as political symbols, the use of weapons and conduct at meetings may reveal deeper attitudes to acceptable behaviour during aggressive political confrontation.